Embedded trials within national clinical audit programmes: A qualitative interview study of enablers and barriers - Alderson, Sarah; Willis, Thomas A; Wood, Su; Lorencatto, Fabiana; Francis, Jill; Ivers, Noah; Grimshaw, Jeremy; Foy, Robbie (Journal of health services research & policy, 2022)
Audit and feedback entails systematic documentation of clinical performance based on explicit criteria or standards which is then fed back to professionals in a structured manner. There are potential significant returns on investment from partnerships between existing clinical audit programmes in coordinated programmes of research to test ways of improving the effect of their feedback to drive greater improvements in health care delivery and population outcomes. We explored barriers to and enablers of embedding audit and feedback trials within clinical audit programmes. We purposively recruited participants with varied experience in embedded trials in audit programmes. We conducted qualitative semi-structured interviews, guided by behavioural theory, with researchers, clinical audit programme staff and health care professionals. Recorded interviews were transcribed, and data coded and thematically analysed. We interviewed 31 participants (9 feedback researchers, 14 audit staff and 8 healthcare professionals, many having dual roles). We identified barriers and enablers for all 14 theoretical domains but no relationship between domains and participant role. We identified four optimal conditions for sustainable collaboration from the perspectives of stakeholders: resources, that is, recognition that audit programmes need to create capacity to participate in research, and research must be adapted to fit within each programme's constraints; logistics, namely, that partnerships need to address data sharing and audit quality, while securing research funding to ensure operational success; leadership, that is, enthusiastic and engaged audit programme leaders must motivate their team and engage local stakeholders; and relationships, meaning that trust between researchers and audit programmes must be established over time by identifying shared priorities and meeting each partner's needs. Successfully embedding research within clinical audit programmes is likely to require compromise, logistical expertise, leadership and trusting relationships to overcome perceived risks and fully realise benefits.